Experimental Investigation of the Impact of Binder Composition and Hemp Hurd Particles on the Mechanical and Hygrothermal Performance of Hempcrete - Ataebi, Elmira (Université d'Ottawa / University of Ottawa, 2025)
Hempcrete, as a lightweight bio-based material, is increasingly gaining attention due to its decarbonization potential in the construction sector. The wooden-structured hemp hurd, combined with a lime-based binder and cementitious materials in the presence of water, forms a durable composite with excellent insulation properties and the ability to provide indoor hygrothermal comfort. This study aims to minimize the environmental impact of hempcrete by using locally sourced materials and increasing the proportion of bio-aggregate in the mixture. The research also seeks to address a gap in the literature by offering a more reliable comparison between various hempcrete binder compositions. This objective is achieved by isolating variables such as density, hemp hurd particle size distribution, and the dominant molar ratio in the binder mix design. The experimental study was conducted using standardized, finely ground hemp hurd, with a hemp-to-binder ratio of 1:1 by weight and a target density of 190 kg/m³. Fifteen distinct hempcrete mix designs were developed using hydrated lime paired with five different supplementary cementitious materials (SCMs), including metakaolin, pumice, silica fume, slag, and Portland cement (as the reference SCM). The mixtures were formulated based on an innovative approach, using the CaO/SiO₂ molar ratio of the binders, and compared with conventional percentage-based binder formulations. Furthermore, hempcrete made with finely ground hemp hurd was compared to that made with conventional, as-received hemp hurd to further investigate the effect of particle size distribution. The comparisons were conducted in terms of mechanical and hygrothermal properties. The results indicated an improvement in mechanical strength with the introduction of SCMs into the binder mixture. However, after reaching an optimal point, further increases in SCM content led to a decline in mechanical performance. Replacing hydrated lime with SCMs based on the CaO/SiO₂ molar ratio of the binder resulted in more consistent mechanical behaviour compared to conventional percentage-based mix designs. Furthermore, increasing the SCM content was found to increase thermal conductivity while reducing the heat capacity of the hempcrete. The incorporation of SCMs in the hempcrete composition demonstrated improved performance in both mechanical and hygrothermal properties compared to the control samples, with metakaolin outperforming all other SCMs. In addition, hempcrete made with finely ground hemp hurd exhibited lower mechanical behaviour but superior insulation performance. Overall, the outcomes of this study provide new insights into more effective comparison methods for hempcrete components and contribute to a better understanding of the material's properties.
Keywords: Hempcrete; Hemp-lime concrete; Bio-based construction material; Hygrothermal properties; Mechanical properties; Metakaolin; Pumice; Silica fume; Slag; CaO/SiO₂ molar ratio